MILITER, ICMI DAN KEBANGKITAN KELAS MENENGAH MUSLIM : RESPON MILITER TERHADAP IKATAN CENDEKIAWAN MUSLIM INDONESIA - Akhmad Satori (Jurnal Ilmu Politik dan Pemerintahan, 2011)
ICMI's emergence as a new political force in the political scene in Indonesia, can not be separated from the pros and cons. among the pro, saw a moderate rise of ICMI that may on the one hand as the government's strategy with its interests, but on the other Muslims also have the advantage in it. While among those who behave counter to the criticism that ICMI ICMI when too close to the bureaucracy in fear will strengthen the symptoms of exclusivism and elitism will even damage the roots of Islamic culture that had been painstakingly built. In addition ICMI criticized as a tool for successful elections in order to later re-elected Soeharto to become President.Military (ABRI), which since the early days of independence until the New Order played an important political role, it also provides a response to the rise of Islamic groups, particularly with regard to the birth of this ICMI.